Observations of surface drift and effects induced by wind and surface waves in the Baltic Sea for the period 2011–2018. (5th February 2021) - Delpeche-Ellmann, Nicole; Giudici, Andrea; Rätsep, Margus; Soomere, Tarmo
Abstract: This study examines one of the longest collection of in-situ surface drifters, deployed at different seasons for the period of 2011–2018 in the Gulf of Finland, Baltic Sea. Overall 38 drifters deployed in batches of three were designed to capture the surface drift in the uppermost 2 m layer of the sea. The properties of drifter trajectories and the effects of wind and waves on the surface drift are analysed both qualitatively and quantitatively. The overall transport is asymmetric and the prevailing direction is out of the gulf against predominant winds. The most frequent drifter speed was 0.05–0.15 m/s (49% of occurrences) and wave height less than 0.5 m (46% of occurrences). Larger drifter speeds generally occurred during periods of stronger winds and higher waves. Wave heights >0.5 m and surface drift >0.15 m/s accounted for 21% of occurrences. In some occasions relatively high drifter speeds (>0.15 m/s) occurred under low wind and in almost calm sea (wave height of <0.5 m). These occasions accounted for 7% and 14% of occurrences, respectively. Rapid motions of drifters were apparently governed by other processes (e.g., eddies, fronts, upwellings, downwellings) during such episodes. For 68% of occurrences the surface current speed is 1.5% of the wind speed with an error of less than ±0.1 m/s. These results demonstrate that whilst wind and surface waves largely govern the surface drift on >2/3 of the occasions, underlying circulation may often dominate the motions in the uppermost layer in the study area. Highlights: Observations of the longest collection of in-situ surface drifters, in the Gulf of Finland, Baltic Sea (2011–2018). Surface current speed of 0.05–0.15 m/s is most prevalent in the Gulf of Finland. An express estimate of the surface current speed as 1.5% of the wind speed is a reasonable estimate for 68% of occurrences with an error of less than 0.1 m/s. Wave height >0.5 m and drift speeds greater than 0.15 m/s occurs, accounted for 21% of occurrences. For about 7–14% of the occurrences the drift is governed by other processes (e.g. eddies, fronts, upwellings) than direct wind and wave impact.